COMPREHENSIVE ASSESSMENT OF THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND MATERIAL WELFARE - Yuliia Prydannykova (Economics & Education, 2018)
This article proposes the contemporary statistical methodology for assessment of relationship between economic growth and material welfare of the Ukrainian regions in 2016 by using the method of complex statistical coefficients. The theoretical and applied aspects of opportunities of studied method for comprehensive rating assessment of Ukrainian regions through standardizing the values of examined indexes in economic and material welfare spheres are considered. Structured and logical schema of mutual influence between the spheres of economics and material welfare of a population is suggested by the author. It was found that the standard of living of a population directly generates material welfare that in turn to be a background for a quality of life. At the same time such distribution of macroeconomic definitions is a new approach enable for statistical studying of relationship between the state of economy and the sphere of material welfare of Ukrainian population. Rating assessment is calculated by available statistical data obtained from the results of state statistical observation performance. The article proclaims that statistical studying of correlation between indexes of economic sphere and indexes in the sphere of material welfare is necessary. For that purpose, it has been developed the way of assessment the degree of relationship of studied spheres based on complex weighted coefficient of variances according to the formula proposed by the author. From the results of calculations of that coefficient and according to the criteria for assessing the stability of a correlation it is justified that the gap between the levels of economic development and material welfare of a population of Ukrainian regions should be reduced. Such approach is considered to determine exact tasks for public administration policy to increase economic growth in relationship with material welfare of a population.